Changes in COVID-19 vaccine acceptance rate among recovered critically Ill patients: A 12-month follow-up study. Issue 48 (26th November 2021) - Olanipekun, Titilope; Abe, Temidayo; Effoe, Valery; Westney, Gloria; Snyder, Richard
Abstract: Introduction: We surveyed a cohort of patients who recovered from severe SARS-CoV-2 infection to determine the COVID-19 vaccination rate. We also compared the willingness to accept COVID-19 vaccine before and after its availability to assess changes in perception and attitude towards vaccination. Materials and Methods: Recovered patients with severe hypoxemic respiratory failure from SARS-CoV-2 infection treated in the ICU at Grady Memorial Hospital, Atlanta, Georgia between April 1, 2020, and June 30, 2020 were followed up over a 1-year period to assess vaccine acceptability and acceptance rates, and changes in perception towards COVID-19 vaccination before and after vaccine availability. Results: A total of 98 and 93 patients completed the initial and follow up surveys respectively. During the initial survey, 41% of the patients intended to receive vaccination, 46% responded they would not accept a vaccine against COVID-19 even if it were proven to be 'safe and effective 'and 13% undecided. During the follow up survey, 44% of the study cohort had received at least one dose of a COVID-19 vaccine. Major reasons provided by respondents for not accepting COVID-19 vaccine were lack of trust in the effectiveness of the vaccine, pharmaceutical companies, government, vaccine technology, fear of side effects and perceived immunity against COVID-19. Respondents were more likely to be vaccinated if recommended by their physicians (OR 6.4, 95% CI 2.8–8.3), employers (OR 2.5, 95% CI 1.9–5.8), and family and friends (OR 1.6, 95% CI 1.1–4.5). Conclusion: We found a suboptimal COVID-19 vaccination rate in a cohort of patients who recovered from severe infection. COVID-19 vaccine information and recommendation by healthcare providers, employers, and family and friends may improve vaccination uptake.